The Impact of Government Regulations on Forest Fires on the Decline in Livelihoods of Residents in Pulang Pisau - Millenia Ardhia Garini; Miki Sepriadi; Enjelita Enjelita; Saputra Adiwijaya; Osi Karina Saragih; Muhammad Zusanri Batubara (Westscience Press, 2024)
Forest fires in Indonesia, especially in peatlands such as Pulang Pisau, Central Kalimantan, are a serious problem that impacts the environment and the livelihoods of local communities that depend on agriculture and timber mining. The government has issued strict regulations based on Law Number 32 of 2009, Law Number 41 of 1999, and Government Regulation Number 10 of 2010 to prohibit forest burning to protect the environment. However, the implementation of these regulations often does not take into account local conditions, leading to a decline in livelihoods, poverty, and population migration. This study uses a descriptive qualitative method to analyze the impact of government regulations on forest fires and livelihood decline in Pulang Pisau. Data were collected through observation, interviews, and document analysis. The results of the study show that the regulation limits the traditional practices of communities in managing land, causing a decrease in income and increasing poverty. Community adaptation to these regulations includes diversification of income sources, training, use of technology, and increased community cooperation. The study recommends increased support through proper training, access to environmentally friendly agricultural technologies, and better coordination between central and local governments. A holistic approach is needed to balance environmental protection and the economic well-being of the community. Effective regulatory implementation and ongoing support are expected to reduce forest fires without sacrificing the livelihoods of local communities.